Developing Supplementary English Material Based On Project Based Learning For Nursing Students Of Medical Department Of Smk Citra Semesta Indonesia Yogyakarta - Pravitasari, Hikmah; , Prof. Dr. Endang Fauziati, M. Hum (2017)
This research aims at developing Supplementary English Material to fulfil the students' need toward the material at vocational high school using Projectbased Learning (PBL). It was conducted to investigate (1) the quality of the existing course book used in SMK Citra Semesta Indonesia (CSI) Yogyakarta, and (2) the development of the Supplementary Project book in SMK CSI Yogyakarta. This research was categorized into Research and Development (R & D). It was conducted in two steps, they were exploration and development. The exploration step revealed: (1) the description of the existing course book used in SMK CSI Yogyakarta and (2) the need analysis of the ESP learning material for students of nursing study program. While the development step explained: (1) the description of the draft of supplementary project book, (2) the result of the trial of the draft, and (3) the final draft of supplementary project book. The data in the exploration stage were collected through conducting document analysis, observation, questionnaire, and having interview. It was carried out to reveal the quality of existing course book used in SMK CSI Yogyakarta and the learner's need toward the material. The findings show that the existing course book contains general English material and it is less specific to be used for the students of nursing skill program. Hence, the findings imply the supplementary project book was needed to be developed by considering the need of the teacher and the students. The supplementary project book was developed by considering some aspects. It contains theoretical theories of ESP and PBL. Then, it was validated and reviewed by some experts in English Language Teaching (ELT), expert of Nursing, and expert of layout. After obtaining the feedback from the experts, then the researcher revised the prototype. To get the feasible product, the prototype was implemented three times in the classroom. Through conducting observation, distributing questionnaire, and having focus group discussion that involved the researcher, the teacher, and students, the draft was revised to be the final draft of supplementary project book. Therefore, after going through the stages, it could be said that the draft is feasible to be applied as supplementary material to teach students of nursing skill program in vocational high school. It is expected that the book can give some contribution and improvement for English teaching and learning.